Cancer Cell Signaling : methods and protocols - Terrian, David M; Ed (Methods in molecular biology (Clifton, N.J.), v. 218., 2003)
Cancer Cell Signaling: Methods and Protocols brings together several such methods in cell signaling research that are scientifically grounded within the cancer biology field.